Tema Harmony in Diversity Perkuat Image Dewarna Hotel & Convention - Vincentia Audrey Ruddy Soetjipto; Tri Noviyanto Utomo; Maria Yohana Susan (KREASI, 2015)
The hotel business is a steadily growing business in Indonesia, especially in tourism cities. InBojonegoro, the hotel business is growing exponentially as the need for business facilities continue to grow over the past few years, mainly because of the Blok Cepu Project. The Blok Cepu Project is an area filled with oils and minerals which spans from Bojonegoro to Tuban – East Java. With this demand specifically situated in Bojonegoro, De Warna Hotel & Convention – a branch from it’s original hotel in Malang – would like to offer business hotel concept which serves a plethora facilities including café, convention room and pool as a form of leisure for hotel guests. With a colorful GSM (Graphic Standard Manual), De Warna Hotel & Convention would like to exude a cheerful ambience in the hotel in hopes of aspiring positives energy to all it’s visitors. As the interior consultant of De Warna Hotel & Convention, Audrey Interior Studio would like to present the concept of Harmony in Diversity in which the fusion of various colours, room functionalities, and intricate architecture would present a sense of harmony without exaggeration. Neutral colors were used as the base and GSM (Graphic Standard Manual) colours were applied to the furniture to further accentuate the room. As to highlight the local aspects of Bojonegoro, local thematic designs which were implemented as the café was designed to introduce Bojonegoro as an oil fields city to visitors especially expatriates.